Effects of the Ti/Fe ratio on the phase composition and magnetic properties of mechanochemically activated Ti–Fe2O3 mixtures - Botta, Pablo Martín (2012)
The mechanochemical activation of Ti/Fe2O3 powder mixtures with molar ratio 1 and 1.5 was performed with the aim of understanding the effects of the starting composition on the reactivity and structure of the produced phases. The solid mixture was characterized by scanning electron microscopy, X-ray diffraction, vibrating sample magnetometry and Mössbauer spectroscopy. The consumption of the reactants and the formation of metallic iron are observed at short activation times. After 3 h, the redox reaction completes, yielding a composite powder formed by nanocrystalline Fe particles dispersed in an oxide matrix. The mixture with the highest Ti/Fe ratio leads to the formation of a TiO2 matrix, whereas the other composition forms FeTiO3. Both composite materials have very high saturation magnetization and moderate coercivities. Under subsequent thermal treatment at 700 °C, the activated solids show a progressive crystalline ordering with partial oxidation of Fe (mainly to FeTiO3 and Fe2O3) and crystallization into the rutile phase of TiO2. This leads to a significant decrease of magnetization and coercivity.